Insulin receptor plays a central role in skin carcinogenesis by regulating cytoskeleton assembly. Issue 2 (17th October 2018) - Weingarten, Galina; Yaakov, Aya Ben; Dror, Erez; Russ, Jenny; Magin, Thomas M.; Kahn, C. Ronald; Wertheimer, Efrat
ABSTRACT: Diabetes mellitus prevalence is increasing rapidly and is a major cause of mortality and morbidity worldwide. In addition to the known severe complications associated with the disease, in recent years diabetes has been recognized as a major risk factor for cancer. Patients with diabetes experience significantly higher incidence of and higher mortality rates from many types of cancer. However, to date there are no conclusive data on the pathophysiology underlying the association between these two diseases. We previously reported that insulin regulates skin proliferation and differentiation, while IGF1 had different sometimes contrasting effects to those of insulin, suggesting direct involvement of insulin in transformation. To this end, we developed an epidermal skin‐specific insulin receptor knockout (SIRKO) mouse, in which the insulin receptor (IR) is inactivated only in skin, with no other metabolic consequences. We found that IR inactivation by itself resulted in a marked decrease in skin tumorigenesis. In the control group 100% of the mice developed tumors, but in the SIRKO group tumor incidence was over 60% lower, and 25% of the SIRKO mice did not develop tumors at all, and the tumors that did develop were smaller and benign in their appearance. Furthermore, IR inactivation in vitro not only prevented cell transformation but also reversed the keratinocyte‐transformed phenotype. We found that IR inactivation led to a striking abnormality in the major keratin cytoskeleton filaments structure in both in vivo and in vitro, a change that we were able to link to the decreased transformation potential in IR‐null cells. In summary, we identified a unique pathway in which IR regulates cytoskeletal assembly, thus affecting skin transformation, opening a new potential target for cancer treatment and prevention.—Weingarten, G., BenYaakov, A., Dror, E., Russ, J., Magin, T. M., Kahn, C. R., Wertheimer, E. Insulin receptor plays a central role in skin carcinogenesis by regulating cytoskeleton assembly. FASEB J. 33, 2241–2251 (2019). www.fasebj.org